Distinct patterns of skeletal muscle mitochondria fusion, fission and mitophagy upon duration of exercise training. (14th September 2018) - Arribat, Yoan; Broskey, Nicholas T.; Greggio, Chiara; Boutant, Marie; Conde Alonso, Sonia; Kulkarni, Sameer S.; Lagarrigue, Sylviane; Carnero, Elvis A.; Besson, Cyril; Cantó, Carles; Amati, Francesca
Abstract: Aim: Healthy ageing interventions encompass regular exercise to prevent mitochondrial dysfunction, key player in sarcopenia pathogenesis. Mitochondrial biogenesis has been well documented, but mitochondrial remodelling in response to exercise training is poorly understood. Here we investigated fusion, fission and mitophagy before and after an exercise intervention in older adults. Methods: Skeletal muscle biopsies were collected from 22 healthy sedentary men and women before and after 4 months of supervised training. Eight lifelong trained age‐ and gender‐matched volunteers served as positive controls. Transmission electron microscopy was used to estimate mitochondrial content. Western blotting and qRT‐PCR were used to detect changes in specific proteins and transcripts. Results: After intervention, mitochondrial content increased to levels of controls. While enhancement of fusion was prevalent after intervention, inhibition of fission and increased mitophagy were dominant in controls. Similarly to PARKIN, BCL2L13 content was higher in controls. The observed molecular adaptations paralleled long‐term effects of training on physical fitness, exercise efficiency and oxidative capacity. Conclusions: This study describes distinct patterns of molecular adaptations in human skeletal muscle under chronic exercise training. After 16 weeks of exercise, the pattern was dominated by fusion to increase mitochondrial content to the metabolic demands of exercise. In lifelong exercise, the pattern was dominated by mitophagy synchronized with increased fusion and decreased fission, indicating an increased mitochondrial turnover. In addition to these temporally distinct adaptive mechanisms, this study suggests for the first time a specific role of BCL2L13 in chronic exercise that requires constant maintenance of mitochondrial quality.